Science anthropologique et racisme à l’époque de l’expansion coloniale : le cas du Grand dictionnaire universel du XIXe siècle de Pierre Larousse - Simoni, Pierre (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1980)
RésuméAlthough colonial expansion in the nineteenth century has usually been viewed in terms of "social imperialism", the contact with non-European peoples also resulted in the formulation of an anthropological science which translated inferiority in technical skills and material possessions into racial terms. Such theories were used to justify colonialism, especially the subjugation of "inferior" races. On the home front, they also provided a framework for depicting class structures. A study of Le Grand Dictionnaire of Pierre Larousse, a vast compendium of left republican beliefs, illustrates these links between anthropological science, racist notions, progress, and imperialism, while at the same time bringing out the tensions between the ideals of progress and perfectability.By analyzing the ideological assumptions laying behind many of the articles in this influential Dictionnaire, the author demonstrates how various anthropological concepts influenced French thought over a wide spectrum of issues. He also draws parallels between French ideas on anthropology, race, imperialism, and social reform, and similar currents of thought in the Anglo-Saxon world.